2006
DOI: 10.1007/s10528-006-9050-1
|View full text |Cite
|
Sign up to set email alerts
|

A Widely Applicable Protocol for DNA Isolation from Fecal Samples

Abstract: Feces are increasingly used as sources of DNA for genetic and ecological research. This paper describes a new method for isolation of DNA from animal feces. This method combines multiple purification steps, including pretreatment with ethanol and TE, an inhibitor-absorber made of starch, the CTAB method, the phenol-chloroform extraction method, and the guanidinium thiocyanate-silica method. The new method is efficient according to PCR results of 585 fecal samples from 23 species and costs much less than the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 24 publications
2
86
0
3
Order By: Relevance
“…In our laboratory the stool kit extracted samples cost over NZ $ 11, labour costs excluded, and the extraction cost of the swabbed samples was approximately NZ $ 5.7. Zhang et al (2006) found the stool-kit to fail for some herbivorous animals, in agreement with our fi nding of the three species of herbivore showing the greatest diff erence in terms of target DNA concentration and PCR inhibition. Although the stool-kit procedure could be partially automated by performing the second half of the extraction in a QIAcube (Qiagen), the fi rst half (sample processing and inhibitor removal) had to be done manually.…”
Section: Dna Extraction Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…In our laboratory the stool kit extracted samples cost over NZ $ 11, labour costs excluded, and the extraction cost of the swabbed samples was approximately NZ $ 5.7. Zhang et al (2006) found the stool-kit to fail for some herbivorous animals, in agreement with our fi nding of the three species of herbivore showing the greatest diff erence in terms of target DNA concentration and PCR inhibition. Although the stool-kit procedure could be partially automated by performing the second half of the extraction in a QIAcube (Qiagen), the fi rst half (sample processing and inhibitor removal) had to be done manually.…”
Section: Dna Extraction Methodssupporting
confidence: 88%
“…Problems caused by coextracted inhibitors, together with DNA degradation and low template DNA concentrations, range from amplifi cation failure to allelic dropout and peak imbalance (Opel et al 2010). Removal of inhibitors normally involves an extra step of incubation with materials such as InhibitEX tablets (Qiagen, Hilden, Germany) or starch (Zhang et al 2006, Kawamoto et al 2013. Alternatively, partial inhibition can be circumvented by diluting the extract and increasing the number of cycles in the PCR, although this can result in higher rates of amplifi cation failure and genotyping errors (Fernando et al 2003).…”
mentioning
confidence: 99%
“…This could be attributed to the quantity of original sample, as in some cases the cloacal swabs contained only small quantities of faeces. Other studies have also reported a correlation between the amount of the faecal material and DNA yield (Ariefdjohan et al, 2010;Zhang et al, 2006).…”
Section: Page | 106mentioning
confidence: 88%
“…В первой серии экспериментов мы исследовали, влияет ли количество взятого в анализ кала на регистрируемое в последствии относительное содержание геномной ДНК человека. В различных работах по метагеномному анализу микробиоты кишечника человека исследуют навески от десятков миллиграммов до нескольких граммов [4,14,19,20]. В настоящей работе мы отобрали пять навесок по 100 мг и выделяли ДНК из каждой независимо, согласно методу 1, ранее используемому в нашей практике [15].…”
Section: кострюкова и дрunclassified